GENERALIZATION OF GOLDBACH’S CONJECTURE AND SOME SPECIAL CASES - Mittas, Ioannis (Italian Journal of Pure and Applied Mathematics, 2010)
Concerned with Goldbach's conjecture, we accomplished a generalization that we called generalized Goldbach's conjecture and proved their equivalency. However, the generalized Goldbach's conjecture reveals a new direction for a potential generalized proof. In this paper we prove both claims for certain cases.